Analisis Kinerja Keuangan Sebelum Dan Selama Pandemi Covid-19 Pada Perusahaan PT Kalbe Farma Tbk - Srisetyawanie Bandaso; Ellyn Patadungan; Ratna Grace (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The purpose of this research is to find out the financial performance of PT Kalbe Farma before and during the pandemic. This research is quantitative. The results showed that the liquidity ratios which included current ratios were 4.35, 4.12 and 4.45, quick ratios were 2.90, 2.98 and 3.01, cash ratios were 117%, 164% and 176% indicating Kalbe Farma's financial performance was liquid before and during the pandemic. Solvability ratios include debt to asset ratios namely 17.76%, 19% and 17.14%, debt to equity ratios namely 21.30%, 23.46% and 20.69% indicating that financial performance was in good condition before and during a pandemic because the industry average is above the ratio value. Profitability ratios including GPM indicate that the company's financial performance is in good condition, namely 45.25%, 44.33% and 42.79%. for NPM 11.21%, 12.11% and 12.31%, ROA is 12.52%, 12.40%, 12.59% and ROE is 15.19%, 15.32% and 15.20% shows that financial performance was not good before and during the pandemic. Activity ratios include inventory turnover 3.3, 3.5 and 2.9, receivables turnover 6.12 times, 5.8 times and 7.4 times, fixed asset turnover 2.5, 2.4 and 2.6 while total asset turnover of 1.1 and 1.02 respectively shows that Kalbe Farma's financial performance is not good enough in managing its assets both during the pandemic in 2020 and 2021 and before the pandemic in 2019